2016
DOI: 10.1016/j.rpor.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in automatic image registration between MV cone beam computed tomography and planning kV computed tomography in image guided radiotherapy

Abstract: This study shows that the automatic IR is accurate within 2 mm and provides confidence in performing them between planning kV CT and MV CBCT image datasets for online image guided radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Most of the data points fell within the ±2 mm bound lines, which represented the upper range of the typical inter‐observer variation of manual image registration in lung SBRT. 8 , 16 , 17 Two patients (6.3%) had translational uncertainty > 2 mm (max = 3.1 mm), and both occurred in the longitudinal direction. Meanwhile, corresponding errors from the direct HCT–CBCTtx auto‐registration, represented by blue colors, were −0.4±2.6, −0.2±7.4, −1.4±3.6 mm, respectively, with 11 patients (34.4%) had translation error > 2 mm (max = 26.2 mm) in at least one direction.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data points fell within the ±2 mm bound lines, which represented the upper range of the typical inter‐observer variation of manual image registration in lung SBRT. 8 , 16 , 17 Two patients (6.3%) had translational uncertainty > 2 mm (max = 3.1 mm), and both occurred in the longitudinal direction. Meanwhile, corresponding errors from the direct HCT–CBCTtx auto‐registration, represented by blue colors, were −0.4±2.6, −0.2±7.4, −1.4±3.6 mm, respectively, with 11 patients (34.4%) had translation error > 2 mm (max = 26.2 mm) in at least one direction.…”
Section: Resultsmentioning
confidence: 99%
“…were used because they are significantly different compared to the density of the surrounding tissues and do not change significantly with the passage of treatment. The analysis of 160 sets of registration data of 8 patients with lung cancer using different registration methods suggested that thoracic vertebrae can be used for the image guidance of lung cancer images guided radiotherapy [24]. The study of CBCT image registration in 25 patients with lung cancer found that the results of central type and peripheral type registration are different.…”
Section: Methodsmentioning
confidence: 99%
“…The manual matching required significantly more time as compared to automatic matching. [15] The gray value ( T + R ) registration algorithm used gray value “correction ratio” procedure for automatic registration. The gray value intensity matching of the voxels in the registration volume was performed during the registration process.…”
Section: Methodsmentioning
confidence: 99%